A Bibliometric Analysis of Burnout in the Creative Industries - Tory, Tingka Febry (Westscience Press, 2025)
Burnout in the world of work is inevitable due to the workload and responsibilities that must be completed, especially in the creative industry, which is physically and mentally draining due to the expectations of many related actors. This study used bibliometric analysis to investigate the literature on burnout in the creative industries, aiming to understand the existing research landscape and identify its practical implications. The analysis uncovered key risk factors, effective intervention strategies, and the most vulnerable groups of workers. The findings provide vital information for policymakers, managers, and practitioners to develop effective strategies to prevent and address burnout in the creative industries.